Family practive physicians', nurse practioners', and physician assistants' spiritual care. - Chapek, Cynthia (My University, 2008)
Several studies have indicated strong relationships between spirituality and health status and lower rates of mortality. The objective of this phenomenological study was to examine how primary care providers incorporate spirituality into their practice.
Color poster with text describing research conducted by Cynthia Chapek under the supervision of Joan Stehle Werner.
Keywords: Medicine--Religious aspects.; Nursing--Religious aspects.; Spirituality--Health aspects.; Posters.